Evaluation of the Disease Activity index for PSoriatic Arthritis (DAPSA) with a quick quantitative C reactive protein assay (Q-DAPSA) in patients with psoriatic arthritis: a prospective multicentre cross-sectional study. Issue 2 (2nd November 2022) - Proft, Fabian; Schally, Julia; Brandt, Henning Christian; Brandt-Juergens, Jan; Burmester, Gerd Rüdiger; Haibel, Hildrun; Käding, Henriette; Karberg, Kirsten; Lüders, Susanne; Muche, Burkhard; Protopopov, Mikhail; Rademacher, Judith; et al.
Abstract : Objectives: This study aimed to evaluate the Disease Activity index for PSoriatic Arthritis (DAPSA) based on a quick quantitative C reactive protein (qCRP) assay (Q-DAPSA) in a multicentre, prospective, cross-sectional study in patients with psoriatic arthritis (PsA). Methods: The assessment of prospectively recruited study patients included joint examination and patient reported outcome (PRO) measures (patient global assessment, patient pain assessment). Following, the DAPSA based on a routine laboratory CRP measurement, Q-DAPSA and clinical DAPSA (cDAPSA) were calculated. Cross-tabulations and weighted Cohen's kappa were performed to analyse the agreement of disease activity categories. Bland-Altman plots and intraclass correlation coefficients were used to determine the agreement of numerical values regarding CRP and qCRP as well as different disease activity scores. Results: Altogether, 104 patients with PsA could be included in the statistical analysis. With Q-DAPSA, 102 of 104 (98.1%) patients achieved identical disease activity categories in comparison to DAPSA with a weighted Cohen's kappa of 0.980 (95% CI: 0.952 to 1.000). The agreement between DAPSA and cDAPSA was slightly lower with identical disease activity categories seen in 97 of 104 (93.3%) of patients and with a weighted Cohen's kappa of 0.932 (95% CI 0.885 to 0.980). Conclusions: The Q-DAPSA showed an almost perfect agreement with the conventional DAPSA regarding identical disease activity categories. Thus, the Q-DAPSA can be used as a timely available disease activity score in patients with PsA with the additional benefit of CRP involvement. Consequently, the Q-DAPSA could facilitate the implementation of the treat-to-target concept in clinical routine and clinical trials.